Cafe Marketing Strategy in Indonesia to Increase Brand Awareness - Prasloranti, Zahra Pitaloka; Hartati, Sri (Business Education Program of Universitas Pendidikan Indonesia, 2024)
The marketing tactics used by Indonesian cafés to raise brand awareness are examined in this study. The study analyzes important marketing strategies that have been successful in raising brand awareness and customer engagement through a combination of bibliometric analysis and literature evaluation. The results emphasize the increasing significance of influencer partnerships, product innovation, social media marketing, and immersive customer experiences as key tactics for increasing brand recognition. Furthermore, implementing sustainability practices and digital loyalty programs improves brand recognition and fortifies consumer relationships. The study comes to the conclusion that cafés looking to stand out in a very competitive industry must adopt a multi-channel, customer-centric strategy. Cafés in Indonesia may greatly increase brand exposure and loyalty by utilizing both digital and physical touchpoints and coordinating marketing initiatives with current consumer trends. The findings offer marketers and café owners useful information for creating winning plans to compete in a market that is getting more and more congested.